2014
DOI: 10.1073/pnas.1318476111
|View full text |Cite
|
Sign up to set email alerts
|

Tracing an allosteric pathway regulating the activity of the HslV protease

Abstract: Significance Molecular machines, such as the proteasome in eukaryotes and archaea as well as the HslU–HslV complex in bacteria, play critical roles in maintaining cellular homeostasis. Here, we have used methyl-Transverse Relaxation-Optimized Spectroscopy to study the 230 kDa HslV dodecamer that cleaves substrate polypeptides. The initial catalytic step is investigated by measuring the pK a of the terminal amine of catalytic residue T1. Furthermore, we show that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 36 publications
0
97
0
Order By: Relevance
“…The proteasomal CP needs to be activated by the 11S activators that bind to both exposed sides of the 7-rings of the CP, inducing allosteric changes within the catalytic chamber as evidenced by methyl-group chemical shift perturbations about 75 Å away from the 11S binding site, and resulting in an alteration of the relative populations of interchanging CP conformers [248]. This distinct allosteric regulation was further shown within HslV, that together with its unfoldase HslU forms a simplified bacterial "proteasome", indicating that the dynamics as well as the plasticity in HslV and the proteasome are critical aspects for the function of these barrel-like proteases [249]. It was also demonstrated that the interior surface of the proteasome stabilizes an unstructured conformation of translocated substrates, thereby preventing refolding of stable protein domains inside the proteasome [250].…”
Section: Proteasomementioning
confidence: 93%
See 1 more Smart Citation
“…The proteasomal CP needs to be activated by the 11S activators that bind to both exposed sides of the 7-rings of the CP, inducing allosteric changes within the catalytic chamber as evidenced by methyl-group chemical shift perturbations about 75 Å away from the 11S binding site, and resulting in an alteration of the relative populations of interchanging CP conformers [248]. This distinct allosteric regulation was further shown within HslV, that together with its unfoldase HslU forms a simplified bacterial "proteasome", indicating that the dynamics as well as the plasticity in HslV and the proteasome are critical aspects for the function of these barrel-like proteases [249]. It was also demonstrated that the interior surface of the proteasome stabilizes an unstructured conformation of translocated substrates, thereby preventing refolding of stable protein domains inside the proteasome [250].…”
Section: Proteasomementioning
confidence: 93%
“…Upon HslU interaction it undergoes concerted millisecond timescale dynamic processes that couple substrate binding and proteolysis to HslU binding [249].…”
Section: Structural Adaptationsmentioning
confidence: 99%
“…Technological advances in structural biology have permitted insights (3)(4)(5) into how changes in protein structure and flexibility contribute to allostery (6)(7)(8)(9). Allostery likely employs a continuum of mechanisms, from domain or subunit rearrangements to predominantly side-chain and backbone dynamics (6-8, 10, 11), to affect biological regulation (1).…”
mentioning
confidence: 99%
“…In the last few years, there have been a number of reports describing clear roles for protein dynamics in allosteric effects, both in the transitions between states and in making substantial contributions to the thermodynamics of the allosteric effect itself (Jiao et al 2012;Kern and Zuiderweg 2003;Law et al 2014;Manley and Loria 2012;McElroy et al 2002;Palazzesi et al 2013;Popovych et al 2006;Rivalta et al 2012;Shi and Kay 2014;Stevens et al 2001). (It is of course difficult to demonstrate the existence of allosteric effects produced solely by changes in dynamics, since the failure to observe a structural change does not mean that it does not occur; Nussinov and Tsai 2014.…”
mentioning
confidence: 99%